Public Relations Strategies in Building the State’s Reputation An analytical study of the publications of the website of the UAE Ministry of Foreign Affairs and International Cooperation - Ibrahim, Rawaa Abdul Rahman; Al-azzawi, Salim Jassem (ALBAHITH ALALAMI, 2022)
The aim of this paper is to know the persuasive methods and public relations strategies in building the reputation of the United Arab Emirates, since the UAE is progressing among the international indicators in good reputation. The researcher used the survey method, using the content analysis tool, to analyze the publications of the UAE Ministry of Foreign Affairs and International Cooperation for the period from 10/1/2021 to 12/31/2021.The researcher reached a set of results, the most important of which are: The UAE Foreign Ministry relied on public relations strategies in order to build a good reputation for the country, as it focused on the media strategy and gave little importance to the consensus-building strategy, as well as focused on emotional, mental and intimidating appeals.